EKSISTENSI HAK WARIS ANAK PEREMPUAN DALAM SISTEM PATRILINEAL BALI: ANTARA NORMA DAN REALITAS - Putu Purnama Dewi; Komang Febriyanti Dantes; Ni Ketut Sari Adnyani (Universitas Pendidikan Ganesha, 2025)
The prominent role of men as primary heirs and lineage bearers within Bali's patrilineal kinship system frequently restricts daughters' access to customary inheritance. This research evaluates the standing of daughters' inheritance rights and investigates the ongoing disparity between customary legal norms and their practical social application. Utilizing a normative legal research methodology grounded in statutory, conceptual, and customary law approaches, data was collected through a comprehensive literature review. Data were obtained through a literature review of regulations, journals, books, and scholarly works relevant to Balinese customary inheritance law. The results of the study indicate that recognition of daughters’ inheritance rights has begun to develop, particularly following the 2010 Decision of the Third Grand Assembly of the Bali MUDP, which provided space for women to receive specific shares of the inheritance. However, its implementation still faces obstacles in the form of a strong patriarchal culture, male-dominated families, differences in village customary regulations (awig-awig), and women’s low willingness to assert their rights. Thus, the existence of daughters’ inheritance rights within Bali’s patrilineal system remains caught between the evolution of customary legal norms and a social reality that has not yet fully reflected equality.